The Representation of Kemayoran International Airport’s Heydey Era Within Hergé's Tintin: Flight 714 To Sydney - Nugroho, Aries Setiawan Satrio; Pratama, Dhika Mega; Savana, Veriza Arrayyan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Tintin is one of the characters created by Herge, a Belgian comic artist. In his comic series, Tintin travels to various countries on his important mission. To find how to construct an understanding to illustrators that a magnificent and monumental illustration work can be achieved with a simple visual style, provided that the illustrator makes a thorough observation of the object to be visualized, so the method used is descriptive qualitative on the panel containing the scene of Tintin at Kemayoran International Airport illustrated in his series entitled Flight 714 to Sydney. The data analyzed includes primary data, namely the Tintin comic flight 714 to Sydney and secondary data such as semiotics and literature review about Kemayoran International Airport, including its important role during its heyday. Before illustrating this airport in detail, Herge has made the most careful observation possible to depict the importance of this place while maintaining the characteristics of his illustrations by using clear lines as its visual identity. By including this airport in his comic creation, Herge directly equates it with famous iconic locations such as Red Square in Moscow, the Giza pyramids in Egypt, and Chateu de Cheverney in France.